2011
DOI: 10.3233/bmr-2011-0281
|View full text |Cite
|
Sign up to set email alerts
|

Psychological status is associated with health related quality of life in patients with rheumatoid arthritis

Abstract: Higher depression and anxiety risks showed increased deterioration in quality of life. Compared to generic QoL scales, RAQoL scale, a disease specific QoL instrument, is much more influenced by depression and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 22 publications
0
31
0
5
Order By: Relevance
“…16 Anxiety has also been found to be associated with poorer QOL. 12,13,17 RA patients with a comorbid psychiatric disorder had lower QOL, 18 and somatization, in particular, was found to be associated with worse QOL, independent of anxiety and depression. 14 Positive social support has been associated with better QOL in patients with RA in some cross-sectional studies, 19 whereas problematic social interactions, criticism, and/or a lack of social support is associated with poorer QOL.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…16 Anxiety has also been found to be associated with poorer QOL. 12,13,17 RA patients with a comorbid psychiatric disorder had lower QOL, 18 and somatization, in particular, was found to be associated with worse QOL, independent of anxiety and depression. 14 Positive social support has been associated with better QOL in patients with RA in some cross-sectional studies, 19 whereas problematic social interactions, criticism, and/or a lack of social support is associated with poorer QOL.…”
Section: Introductionmentioning
confidence: 93%
“…Depressive symptoms and depression have been associated with worse QOL in patients with RA in cross-sectional studies [12][13][14][15] and found to be an independent predictor of QOL at two-year follow-up. 16 Anxiety has also been found to be associated with poorer QOL.…”
Section: Introductionmentioning
confidence: 97%
“…Lo cual se relaciona con diferentes estudios que han puesto de manifiesto niveles significativos (21% a 70%) de la ansiedad en la AR (Covic et al, 2012;Isik, Koca, Ozturk & Mermi, 2007) y la influencia de esta emoción negativa sobre la CVRS (Nas et al, 2011;Ozcetin et al, 2007).…”
Section: Tabla 2 Estadísticos Descriptivos De Las Variables Felicidadunclassified
“…Resultados similares se han encontrado en muestras de enfermos crónicos (Hoppe, 2013;Nas et al, 2011;Ozcetin et al, 2007;Veenhoven, 2008) y en pacientes con dolor crónico (Muller et al, 2015;Tran et al, 2015;Ryan & McGuire, 2015).…”
Section: Tabla 2 Estadísticos Descriptivos De Las Variables Felicidadunclassified
“…We agree that, unfortunately, research on depression screening and management is lacking. Our article was a comprehensive literature review identifying multiple studies that demonstrated that the prevalence of depression in patients with psoriatic disease and RA was higher compared with control groups 9,10,11,12,13,14,15,16,17 . A published metaanalysis that helped corroborate our finding reported an overall depression prevalence of 28% in PsO and that patients with PsO were more likely to have depression than those without PsO (OR 1.57, 95% CI 1.40-1.76) 18 .…”
Section: To the Editormentioning
confidence: 99%